THE INFLUENCE OF KIMEMATICS AND STRUCTURAL ELEMENTS WHILE FORMING THE SHAPE OF SPRINTER'S CURVE OF SPEED DURING RUNNING ON 100 METERS - Veselin Jovović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The speed of running on the track mostly depends on rational moves, capability of running without unneeded exerting, and the runner's level of speed persistence. There is opinion that the best sprinters on l00 m finish their starting acceleration at 22 - 30 metres. Howerer, the analysis shows that in that period sprinter reaches 90-95% of maximum speed. The most sprinters reach the greatest speed only on 50-55 m. After that, maximum speed is kept only on 25-30 m, and after that, mainly, it falls down, and that is because of the difficulty of keeping the optimal frequency and the lenght of steps at the finish of run.